(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2015)
The process of producing mono-alkyl esters of fatty acids from cottonseed and sunflower oils under the influence of the magnetic field with intensityÂ 15-45 mTÂ wasÂ investigated . It was revealed that the use of the energy ofÂ magnetic field allows to reduce the reaction time to 10 times, the excess of used alcohol to 2 times while maintaining high yield of the desired product.